The Allocation Of Low-Cost Housing Units And The Changes On The Socio-Economic Life Of The Residents - Lim, Chye Gaik (Universiti Sains Malaysia, 1982)
This study looks into the criteria for the allocation of the low cost housing units to see how closely the criteria correspond to the ground situation in the case of the low cost housing in Bayan Baru New Town